Right ventricular endomyocardial biopsy in patients with cardiac magnetic resonance showing left ventricular myocarditis. Issue 7 (July 2021) - Peretto, Giovanni; Cappelletti, Alberto M.; Spoladore, Roberto; Slavich, Massimo; Rizzo, Stefania; Palmisano, Anna; Esposito, Antonio; De Cobelli, Francesco; Margonato, Alberto; Basso, Cristina; Della Bella, Paolo; Sala, Simone
Abstract : Aims: The aim of this study was to evaluate the sensitivity of right ventricular endomyocardial biopsy (EMB) in myocarditis patients with cardiac magnetic resonance (CMR) and electroanatomical mapping (EAM) showing left ventricular abnormalities. Methods: We performed right ventricular EMB in 144 consecutive patients (66% men, age 43 ± 15 years) with acute symptoms and CMR-proved diagnosis of left ventricular myocarditis. Right ventricular EMB sensitivity has been evaluated in patients with different localization and extension of abnormal substrate at both CMR and -- when performed -- EAM. Abnormal substrate was defined, respectively, by late gadolinium enhancement (LGE) and low-voltage areas (LVAs). Results: Globally, right ventricular EMB sensitivity was 87.5%. EMB-negative cases had significantly smaller fragment sizes (cumulative area 2.8 ± 1.7 vs. 3.8 ± 1.8 mm 2, P  = 0.023), and lower LGE surface extension (24.7 ± 14.2 vs. 38.5 ± 20.2%, P  = 0.006) and transmurality (32.0 ± 26.1 vs. 49.3 ± 22.6, P  = 0.003). Right ventricular EMB sensitivity in patients with LGE involving both right ventricular and interventricular septum (IVS), isolated right ventricular or IVS, and remote left ventricular areas ( n  = 10, 49 and 67 cases) was 83.3, 84.4 and 90.5%, respectively ( P  = 0.522). Overall, 34 patients (23.6%) underwent EAM. On the basis of EAM, right ventricular EMB sensitivity was 85.3%: in detail, it was 50.0, 88.2 and 86.7% in patients with both right ventricular and IVS, isolated right ventricular/IVS and distant left ventricular involvement ( n  = 2, 17 and 15, respectively, P  > 0.05). Sample size area was the only factor associated with right ventricular EMB sensitivity (hazard ratio = 1.6/mm 2, 95% confidence interval 1.1–2.4, P  = 0.013). Conclusion: Right ventricular EMB is still an accurate technique to confirm diagnosis in patients with CMR-proved left ventricular myocarditis. In particular, provided there is an adequate sample size, its sensitivity is comparable among patients with heterogeneous LGE or LVA localization.